Spring-Interseeded Winter Rye Seeding Rates Influence Weed Control and Organic Soybean Yield - Kelly A. Nelson; Reid J. Smeda; Randall L. Smoot (International Journal of Agronomy)
Field research in 2002 and 2003 evaluated spring-interseeded winter rye (Secale cereale L.) at 67, 134, or 200 kg ha−1 at two soybean (Glycine max (L.) Merr.) row spacings (19- and 76-cm) on weed control, yield, and gross margins. Based on regression analysis, wide-row (76-cm) soybean grain yield and gross margins were greatest when winter rye was interseeded at 114 and 106 kg ha−1, respectively. Yields and gross margins for wide-row soybean were 8 to 55% greater than narrow-row (19-cm) soybean seeded at 494,000 or 742,000 seeds ha−1 which was probably due to flexibility for implementing cultivation. As interseeded rye rates increased from 67 to 200 kg ha−1, yields and gross margins for narrow-rows decreased. Soybean row spacing had minimal impacts on specific weed species and total weed biomass or density. The use of wide-row soybean and spring-interseeded rye at 67 kg ha−1 was more cost-effective compared to narrow rows.